Cardiocutaneous syndrome is caused by aggregation of iASPP mutants - Rebecca Lotz; Christian Osterburg; Birgit Schäfer; Xin Lu; Volker Dötsch (Cell Death Discovery)
Abstract The ASPP (apoptosis-stimulating protein of p53) family of proteins is involved in many cellular interactions and is starting to emerge as a major scaffolding hub for numerous proteins involved in cancer biology, inflammation and cellular integrity. It consists of the three members ASPP1, ASPP2 and iASPP which are best known for modulating the apoptotic function of p53, thereby directing cell fate decision. Germline mutations in iASPP have been shown to cause cardiocutaneous syndromes, a combination of heart and skin defects usually leading to death before the age of five. Mutations in iASPP causing these syndromes do not cluster in hot spots but are distributed throughout the protein. To understand the molecular mechanism(s) of how mutations in iASPP cause the development of cardiocutaneous syndromes we analysed the stability and solubility of iASPP mutants, characterized their interaction with chaperones and investigated their influence on NF-ĸB activity. Here we show that three different mechanisms are responsible for loss of function of iASPP: loss of the complete C-terminal domain, mutations resulting in increased auto-inhibition and aggregation due to destabilization of the C-terminal domain. In contrast to these germline mutations causing cardiocutaneous syndromes, missense mutations found in cancer do not result in aggregation.